Answer:
[tex](f\circ g)(x)=x^2+9x+20[/tex]
Step-by-step explanation:
We have the two functions:
[tex]f(x)=x^2+5x+6\text{ and } g(x)=x+2[/tex]
And we want to find:
[tex](f\circ g)(x)[/tex]
This is equivalent to:
[tex](f\circ g)(x)=f(g(x))[/tex]
Therefore, we will have:
[tex]f(x+2)[/tex]
By substitution:
[tex]f(x+2)=(x+2)^2+5(x+2)+6[/tex]
Simplify. Square and distribute:
[tex]f(x+2)=(x^2+4x+4)+(5x+10)+6[/tex]
Rearrange:
[tex]f(x+2)=(x^2)+(4x+5x)+(4+10+6)[/tex]
Combine like terms:
[tex]f(x+2)=(f\circ g)(x)=x^2+9x+20[/tex]